Natural Decomposer (MOL) developed from various banana waste and different storage times - DEWI YUNITA; IRFAN IRFAN; MARLINA MARLINA (Jurnal Natural, 2021)
MOL is a local microorganism or natural decomposer that is used as a starter culture in production of organic fertilizers which is known as bokashi. The advantage of using MOL is that it can be made from cheap materials or by utilizing agricultural waste so that it can increase the added value of waste as well as reduce the environmental pollution. The use of MOL as a biodecomposer in production of bokashi can accelerate the fermentation process. This study aimed to produce MOL where the characteristic is similar with commercial Effective Microorganism (EM4). This study used a factorial randomized block design (RBD) with 2 factors. First factor was the types of banana (J) consisted of three levels, namely awak banana (Musa paradisiacal var. Awak; J1), barangan banana (Musa acuminate Colla; J2), and kepok banana (Musa acuminata balbisiana Colla; J3). Second factor was the storage times consisted of three levels, namely 0 weeks after fermentation (L1), 2 weeks after fermentation (L2), and 4 weeks after fermentation (L3). The analysis carried out after fermentation included total cell counts (TCC), pH value, temperature, and organoleptic test in the form of hedonic test for color and description test for aroma. The best sample was determined based on the highest TCC, the lowest pH value and aroma using a ranking test. The best treatment was obtained from J1L2 treatment (awak banana and 2 weeks after fermentation) with 1.8 × 109 CFU/ml of TCC, 3.17 of pH and medium tapai aroma.